Prove that the following is true for all n ∈ N(natural numbers)

h^(n)= ∑ (k=0 to n) n!/k!(n-k)!f^(n-k) * g^(k)(x)

Note: We can assume Pascal’s Idenity for 1<(or=)k<(or=)m

- Sep 15th 2010, 09:28 PMsimkate96h^(n)= ∑ (k=0 to n) n!/k!(n-k)!f^(n-k) * g^(k)(x) : Prove that the following is true
Prove that the following is true for all n ∈ N(natural numbers)

h^(n)= ∑ (k=0 to n) n!/k!(n-k)!f^(n-k) * g^(k)(x)

Note: We can assume Pascal’s Idenity for 1<(or=)k<(or=)m - Sep 15th 2010, 10:54 PMProve It
What are $\displaystyle f(x)$ and $\displaystyle g(x)$?

Also this is near impossible to read.

Are you asking to show this?

$\displaystyle \displaystyle{h^n(x) = \sum_{k = 0}^n\frac{n!}{k!(n-k)!}f^{n-k}g^k(x)}$ - Sep 16th 2010, 05:34 AMtonio